2000
DOI: 10.2355/isijinternational.40.779
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Impurities in Graphite and Silicon Carbide by Total Reflection X-ray Fluorescence Spectrometry after Homogeneous Liquid-Liquid Extraction.

Abstract: Using homogeneous liquid-liquid extraction as a pre-concentration method, a determination procedure of trace impurities (Fe, Ni and Cu) by total reflection X-ray fluorescence (TXRF) analysis was developed and optimized for graphite and silicon carbide samples. The samples were decomposed by alkali fusion. The residue was dissolved in a mixture of pentadeca-fluorooctanoic acid (PFOA), acetone and water, and the analytes were homogeneously dispersed by the aid of phenanthroline (phen). After phase separation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Various industrial applications of TXRF spectrometry were reported during the review period. Trace impurities in graphite and silicon carbide were determined after homogenous liquidliquid extraction, which was used as a preconcentration technique by Yamaguchi et al 170 Metal additives and Br in recycled thermoplastics from electronic waste were determined by Fink et al 171 The samples were dissolved in an organic solvent and the corresponding solutions or suspensions subsequently analysed. The authors found this method to be less timeconsuming than the conventional digestion of the polymer matrix.…”
Section: Total Reflection X-ray Fluorescence Spectrometry (Txrf)mentioning
confidence: 99%
“…Various industrial applications of TXRF spectrometry were reported during the review period. Trace impurities in graphite and silicon carbide were determined after homogenous liquidliquid extraction, which was used as a preconcentration technique by Yamaguchi et al 170 Metal additives and Br in recycled thermoplastics from electronic waste were determined by Fink et al 171 The samples were dissolved in an organic solvent and the corresponding solutions or suspensions subsequently analysed. The authors found this method to be less timeconsuming than the conventional digestion of the polymer matrix.…”
Section: Total Reflection X-ray Fluorescence Spectrometry (Txrf)mentioning
confidence: 99%
“…In this context, several analytical techniques have been applied [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The most common approach involves the dissolution of the sample followed by inductively coupled plasma mass spectrometry (ICP-MS) or ICP-optical emission spectrometry (ICP-OES) analysis [ 6 , 16 , 17 , 18 , 19 , 20 ]. The need of samples in solution form is, however, a major limitation when treating SiC ceramics: SiC is extremely inert and difficult to dissolve even under extreme conditions (e.g., high temperatures, presence of concentrated acids and bases).…”
Section: Introductionmentioning
confidence: 99%
“…The need of samples in solution form is, however, a major limitation when treating SiC ceramics: SiC is extremely inert and difficult to dissolve even under extreme conditions (e.g., high temperatures, presence of concentrated acids and bases). This process is, in fact, typically carried out under highly harsh conditions by microwave acid digestion (e.g., H 2 SO 4 + HNO 3 + HF at 230 °C for 20 h [ 16 ] or even at higher temperatures up to 250 °C [ 20 ]) or alkaline melting (e.g., Na 2 CO 3 + Na 2 B 4 O 7 or Li 2 B 4 O 7 in platinum crucibles at 1000 °C for 30 min [ 17 ]). Nonetheless, it should be pointed out that (i) dedicated equipment is required to carry out these extreme dissolution protocols; (ii) the use of alkaline fusion is very limited for the determination of ultra-trace impurities because of the high background signal generated by the significant saline content in solution; (iii) microwave acid digestion may suffer from high blank signals due to the limited purity of the acid mixture (especially that of sulfuric acid, which is essential because of the high temperatures that need to be reached) making the determination of trace elements such as Cu, Fe and Al difficult [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…4) The disadvantages of microwave reflux digestion at ordinary pressure 6,7 are that the operation is cumbersome and time-consuming, and the operation of multiple cooling and adding HNO3 is easy to contaminate the sample. 5) The method of direct injection of sample for determination [7][8][9][10][11] is poor in precision since the sample is directly measured without digestion.…”
Section: Introductionmentioning
confidence: 99%